Wykorzystanie doświadczeń treningu sportowego do rozwoju menedżerów w organizacjach - Cieśliński, Wojciech (The use of sports practice experience in managers' fevelopment in organizations, 2006)
The paper contains a theoretical conception of application of the grounds of periodic sport training to managers’ professional development. The starting point is the assumption that managers are valuable capital and their value should be increased periodically, like sportsmen’s one.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 15-23